2004
DOI: 10.3846/16484142.2004.9637978
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Technological Processes in Terminals

Abstract: In this article technological processes in transport terminals are analysed. A technological scheme of the transport terminal is analysed graphically reflecting the sequence of working operations with regard to aerial location, necessary equipment, outfit and workers. A technological graph chart reflecting the technological acceptability and time normatives of technological operations of a transport process is present. The estimation and adaption of models in transport terminals are presented. A dynamic model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…The equation for the estimation of the extremum of the function (12) with respect to the number of machines at the unloading bay, after the differentiation and corresponding transformations, takes the form:…”
Section: Case Study: Optimizing Resources Of the Amur Harbor Cargo Armentioning
confidence: 99%
See 2 more Smart Citations
“…The equation for the estimation of the extremum of the function (12) with respect to the number of machines at the unloading bay, after the differentiation and corresponding transformations, takes the form:…”
Section: Case Study: Optimizing Resources Of the Amur Harbor Cargo Armentioning
confidence: 99%
“…However, decision-making on the choice of service technologies and the amount of production resources requires preliminary justification using the advanced models of a transport hub functioning. Existing approaches to the modelling of technological processes of transport terminals are mainly based on analytical models [9][10][11][12][13][14] that do not allow researchers to estimate the complex influence of a set of random external factors on the efficiency of the hub's operation. Thus, the research direction of creating new models of operation of transport terminals using modern mathematical methods and information technologies is relevant, and the use of the resulting methodologies can increase the efficiency of the processes of logistics management and ensure the sustainable development of the transport system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A database analysis of studies and scientific papers showed the scarcity of study space dedicated to technological processes for optimization at inland terminals. Jarašūniene's paper [79], for example, examines a particular aspect, concerning optimization of the recognition of vehicles entering the inland terminal: through the development of a dynamic model, the system is able to accelerate the process of controlling entering containers and sending them to the deposit.…”
Section: Technological Processesmentioning
confidence: 99%